New Technologies and the Arms Race
XXVII, 377 p.
Keywords: This volume contains the proceedings of the International Conference on Technology, Arms Race and Disarmament which took place at Castiglioncello, Italy, in September 1987. The papers examine strategic defence policies, nuclear weapons proliferation and arms control among many other topics.